LEGAL FICTION OF SERVICE OF DOCUMENTS IN ADMINISTRATIVE PROCEEDINGS CARRIED OUT BY PUBLIC ORGANS - Dorota HAMERLAK; Magdalena DREWNIANY (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2014)
The aim of the paper is to analyse legal fiction of service of correspondence in accordance with Code of Administrative Proceedings and Tax Law Act. The essence of serving pursuant to Article 44 of Code of Administrative Proceedings and Article 150 of Tax Law Act is storing the correspondence for 14 days at a post office, in case of service conducted by a postal operator, or storing it for 14 days in the commune or town council’s office – in case of service conducted by an employee of the commune or town council or other authorized person or organ (in accordance with Tax Law Act the person conducting the service may also be an employee of Tax Office). The addressee is notified twice about the service by means of a written notification left at his/her letter box or when it is not possible, in the door of his/her place of residence, office or other premises where the addressee performs his/her professional activity or in a noticeable spot at the entrance of his/her property. If the addressee does not report for receipt of the correspondence, the date of service of the correspondence will be the day when the 14 day storing period expires (it is calculated in accordance with Article 57 & 1 of Code of Administrative Proceedings). However, many doubts arise when the correspondence served under this regulation contains a notification about initiation of proceedings and the purpose of sending this correspondence is to establish contact with the Party in order to secure his/her right to active participation in the proceedings. It should be noted here that the way of serving correspondence described above is a mere legal fiction and does not fulfill its intended function. Moreover, in case of return of the correspondence with the note “not collected by deadline”, the administrative organ cannot be sure whether the absence of the addressee is only temporary or the Party does not reside under this address any more or the Party is absent, in which case, in accordance with Article 34 of Code of Administrative Proceedings or Article 138 of Tax Law Act, there is a need to apply to court for establishment of a Proxy for the absent Party.